The Scope and Impact of the COVID-19 Pandemic on Neuroemergent Patient Transfers, Clinical Care and Patient Outcomes - Woodward, Josha; Meza, Samuel; Richards, Dominick; Koro, Lacin; Keegan, Kevin C.; Joshi, Krishna C.; Munoz, Lorenzo F.; Byrne, Richard W.; John, Sayona (Frontiers in Surgery, 2022)
Introduction: The SARS-CoV-2 (COVID-19) pandemic continues to substantially alter previously established clinical practice patterns and has transformed patient care in American healthcare. However, studies to evaluate the impact of COVID-19 on neuroemergent patient care and associated clinical outcomes are limited. Herein, we describe the impact of COVID-19 on the Neuroemergency Transfer Program (NTP) - a novel, urban, high volume interhospital patient transfer program. Objective: To evaluate and describe the clinical impact of the COVID-19 pandemic on the NTP. Study Design: A single-center retrospective study of prospectively collected consecutive neuroemergent patient transfer data between 2018-2021 was analyzed. Adult patients were divided based upon transfer date into a Pre-COVID (PCOV) or COVID cohort. Patient demographics, transfer characteristics and clinical data and outcomes were analyzed. Results: 3,096 patients were included for analysis. Mean age at transfer in the PCOV and COVID cohorts were 62.4±0.36 and 61.1±0.6 years. A significant decrease in mean transfers per month was observed between cohorts (PCOV=97.8 vs. COV=68.2 transfers/month, p<0.01). Total transfer time in the PCOV cohort was 155.1±3.4 minutes which increased to 169.3±12.8 minutes in the COVID cohort (p=0.13). Overall mean transfer distance was significantly longer in the PCOV cohort at 22.0±0.4 miles vs. 20.3±0.67 miles in the COV cohort (p=0.03). The relative frequency of transfer diagnoses was unchanged between cohorts. A significant increase in mean inpatient length of stay was noted, 7.9±0.15 days to 9.6±0.33 days in the PCOV vs. COVID cohorts (p<0.01). Ultimately, no difference in the frequency of good vs. poor clinical outcome were noted between the PCOV (79.8% and 19.4%) vs. COV (78.8% and 20.4%) cohorts. Conclusion: The impact of COVID-19 on current healthcare dynamics are far reaching. Here, we show a significant decrease in interhospital patient transfers and increased length of stay between a Pre-COVID and COVID cohort. Further work to better elucidate the specific interplay of clinical contributors to account for these changes is indicated.